Mahasiswa Sebagai Salah Satu Kekuatan Penegakan Hukum - Layyin Mahfiana (Justicia Islamica, 2004)
This study aims to analyze the role of students as one of the forces in law enforcement in Indonesia. The method used is juridical-sociological research with a descriptive-analytical approach, through literature studies and studies of student movements in the history of legal reform. The results show that students have a strategic role in upholding the rule of law through advocacy, social criticism, and involvement in reform movements. In various historical moments, students have been agents of change that encourage transparency, accountability, and justice in the legal system. However, the challenges faced include the lack of consistency in the movement, political intervention, and limitations in in-depth understanding of the law. Therefore, it is necessary to strengthen students' capacity in understanding the law and more systematic advocacy strategies in order to contribute more effectively to law enforcement.